When margins call: Liquidity preparedness of non-bank financial institutions - Valentina Macchiati; Lorenzo Cappiello; Margherita Giuzio; Annalaura Ianiro; Fabrizio Lillo (European Central Bank (ECB), 2025)
We propose a novel framework to assess systemic risk stemming from the inadequate liquidity preparedness of non-bank financial institutions (NBFIs) to derivative margin calls. Unlike banks, NBFIs may struggle to source liquidity and meet margin calls during periods of significant asset price fluctuations, potentially triggering asset fire sales and amplifying market volatility. We develop a set of indicators and statistical methods to assess liquidity preparedness and examine risk transmission through common asset holdings and counterparty exposures. Applying our framework to euro area NBFIs during the Covid-19 turmoil and the 2022-2023 monetary tightening, we observe an increase in distressed entities, which, in turn, seem to exhibit more liquidity-driven selling behaviours than their non-distressed peers. Network analysis suggests that certain counterparties of distressed entities appear particularly vulnerable to margin call-induced liquidity shocks. Our framework offers policymakers valuable tools to enhance the monitoring and resilience of the NBFI sector.
Keywords: C02; E52; G01; G11; G23; 330; Non-bank Financial Institutions; Derivative margin calls; Liquidity risk; Network analysis; Financial stability; money-market liquidity; financial risk; financial institution; financial market; insurance company; investment company; pension fund; financial derivative; report